(untitled) (Research, Society and Development, 2022)
Based on the principle of “First, do no harm”, the patient safety has been a worldwide target for improvement and implementation on health field and it is still a major challenge for pediatrics due to children’s fragility, vulnerability and specific conditions. To analyze how a caregiver understands the nursing care processes concerning the patient safety practice in order to recommend good future practices which reinforce a humane, safe nursing care, respecting a structured-standard of care. A qualitative descriptive research was conducted with caregivers of children admitted to a university hospital in the metropolitan region of Porto Alegre, Brazil, in April 2019. Data collection was performed by semi-structured interviews. Based on the data analysis, it is possible to identify five categories for standard of care, this is, patient’s identification, medication administration, adherence to infection prevention process, age group and risk of falling, empathy as improvement of patient’s safety. The nurse is the essential professional in the role of educator, by acting in a preventive way, promoting and encouraging good care practices. Besides, this professional can create standard operating programs for care procedures, teach them and train a work team to use these new practices.